(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The introduction of the internet and smart phones has ushered in a new era of shopping. The word "online marketing " refers to a company model in which products and services are provided directly to consumers through a website, eliminating the need for a middleman. E commerce makes it possible for us to order the items we need from the comfort of our own homes. Customers may choose and choose from a wide range of goods accessible online before placing their order. Customers may pay for the goods using a credit card, a debt cart, e-cash, or an e-wallet. These developments in ecommerce, as well as E-Business possibilities and technological advancements, are discussed in this article. This study focused the opinion of online customers availed benefits in Chennai city.